Analysis of the trajectory of aun si in Spanish - Fante, Barbara Ribeiro [UNESP] (2023)
This article presents a diachronic analysis of the trajectory of aun si in Spanish, according to the theoretical assumptions of grammaticalization based on Discursive-Functional Grammar (Hengeveld 2017; Hengeveld y Mackenzie 2008). In the Spanish grammatical tradition, aun si is considered a concessive conditional conjunctive phrase as it operates in both concessive and conditional clauses. The analysis of occurrences from the ancient, middle and modern periods of Spanish show that, in past synchronies, the conditional conjunction si is scoped by aun, while in the modern period there is a fixation of aun and si as attested by the criteria of mobility and de modification applied to the conjunction phrase (Keizer 2007; Giomi 2020). Despite this general tendency, the grammaticality cline of aun si does not fully prove the initial hypothesis that its trajectory starts from the conditional value (in the past periods) and, in the process of grammaticalization, follows towards the concessive value since syntactic, semantic and discursive stability of aun si was verified from the 13th to the 21st century which explains the coexistence, in modern Spanish, of two types of aun si: the conditional and the concessive conditional.